1989
DOI: 10.1111/j.1600-0714.1989.tb01561.x
|View full text |Cite
|
Sign up to set email alerts
|

lnterleukin‐2 mediated regulation of mitogen‐activated T cell reactivity from different lymphoid sources in patients with squamous cell carcinoma of the oral cavity

Abstract: Peripheral blood lymphocytes (PBL) from patients with oral cancer (treated and untreated), oral leukoplakia and healthy donors; lymphocytes from metastatic and non-metastatic lymph nodes (met LNL and non-met LNL); and tumor infiltrating lymphocytes (TIL) were tested for proliferative response to mitogen PHA (phytohemagglutinin) and its augmentation by recombinant Interleukin-2 (rIL-2), for expression of Tac antigen (CD25) and for production of IL-2. Depressed PHA responses were found in PBL of treated and untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Functional studies examining TILs have shown poor response to mitogens and reduced cytotoxicity to autologous tumor 46–56 . CD34+ cells have been identified in TIL and secret immunosuppressive factors that block T cell function 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies examining TILs have shown poor response to mitogens and reduced cytotoxicity to autologous tumor 46–56 . CD34+ cells have been identified in TIL and secret immunosuppressive factors that block T cell function 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from several laboratories suggest that alterations in function and expression of signal transduction molecules associated with TCR are responsible for the deficiencies observed in various cancers (Sebzda et al 1999;Kulkarni et al 2009;Kurt et al 1998). Unfortunately, there are no prospective studies in oral cancer examining the clinical Recent evidence for the presence of functional defects of circulating T cells in patients with head and neck cancer emphasizes the fact that their anti-tumor responses are compromised (Shibuya et al 2002;Nakagomi et al 1993;Buggins et al 2001;Murali et al 1987). It appears that head and neck tumors not only effectively escape from the host immune system but also actively corrupt the host antitumor response via several distinct mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…Role of IL-1 in T cell immune cascade is well documented. In our previous studies we have shown that T cell hyporesponsiveness in oral cancer patients was not directly attributable to abnormalities in the T cell mediated events (10). Therefore, in the present studies, we have tried to investigate the monocyte/macrophage functions in oral cancer patients in response to activation signals.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous studies we have demonstrated that patients with squamous cell carcinoma (SCC) of the oral cavity show depressed T cell responses to mitogens and alloantigens (9). This defect could not be correlated with IL-2 mediated events (10). Impairment of T cell functions in cancer patients could be related to abnormalities in monocyte/macrophage activation and functions, such as changed expression of Fc receptor (FcR) and MHC Class II molecules (11,12), defective interleukin-1 (IL-1)…”
mentioning
confidence: 99%